Man against machine: Debates in the expert community on the lethal autonomous systems - A. Yu. Lipova (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
In the recent years debates surrounding the autonomous weapons systems development and regulation have gained a new momentum. Despite the fact that the development of such type of weapons continues since the twentieth century, recent technological advances open up new possibilities for development of completely autonomous combat systems that will operate without human in-tervention. In this context, international community faces a number of ethical, legal, and regulatory issues. This paper examines the ongoing debates in both the Western and the Russian expert community on the challenges and prospects for using lethal autonomous systems. The author notes that Russian and Western discourses on most of the issues have very much in common and diﬀ erences are found mainly in the intensity of debates — in the West they are much more ac-tive. In both cases the most active debates focus around two issues: the potential implications of fully autonomous weapons systems including the unclear line of accountability, and the prospects for international legal regulation of the use of lethal autonomous weapons. Both the Russian and the Western experts agree that the contemporary international humanitarian law is unable to handle the challenges posed by aggressive development of the lethal autonomous weapons. All this points to the need to adapt the international humanitarian law to the new realities, which, in turn, requires concerted actions from leading states and international organizations.